2017
DOI: 10.3390/app7050474
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Sensitive Optical Coherence Tomography: A Review of Technology and Applications

Abstract: Polarization sensitive optical coherence tomography (PS-OCT) is an imaging technique based on light scattering. PS-OCT performs rapid two-and three-dimensional imaging of transparent and translucent samples with micrometer scale resolution. PS-OCT provides image contrast based on the polarization state of backscattered light and has been applied in many biomedical fields as well as in non-medical fields. Thereby, the polarimetric approach enabled imaging with enhanced contrast compared to standard OCT and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 236 publications
(351 reference statements)
0
99
0
Order By: Relevance
“…6,11,15 On the other hand, the utilization of the DOPU algorithm in combination with PS-OCT is an established concept in ophthalmologic research. 8,16,18 To the best of our knowledge, this is the first time that the DOPU algorithm is applied for the detection of carious lesions in dentistry. We consider it as a promising method for the identification and delimitation of early carious lesions in particular but also the assessment of the severity of an undermining caries and a cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11,15 On the other hand, the utilization of the DOPU algorithm in combination with PS-OCT is an established concept in ophthalmologic research. 8,16,18 To the best of our knowledge, this is the first time that the DOPU algorithm is applied for the detection of carious lesions in dentistry. We consider it as a promising method for the identification and delimitation of early carious lesions in particular but also the assessment of the severity of an undermining caries and a cavity.…”
Section: Discussionmentioning
confidence: 99%
“…This includes polarization sensitive imaging and the consequent measurement of depthresolved birefringence, which until now has been applied in many biomedical as well as nonmedical fields. 8,9 In terms of hard dental tissue and caries detection, first polarization sensitive OCT (PS-OCT) measurements confirmed the birefringent properties of enamel and dentin, 4,10 and it was determined that demineralization, accompanying carious infections, results in depolarization of light. 11 Since then, several studies have shown the potential of PS-OCT to observe the internal structure and the remineralization of lesions, as well as an early detection of variously located caries.…”
Section: Introductionmentioning
confidence: 95%
“…8 Today, this method is referred to as PS OCT with single circular input state, which provides quantitative polarization contrast for all possible optic axis orientations of the sample. 9 Beyond the technical advancements in terms of light sources and fast detection units, PS OCT was evolved by different detection schemes with multiple input states as well as improved data processing. Initially, 7,8 the reflectivity and retardation of a sample were measured for the determination of birefringence as a function of the depth.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] An additional relevant parameter, the degree of polarization uniformity (DOPU), is based on averaged Stokes vector elements and proposed for imaging and segmentation of local variations of the polarization state 13,14 also known as depolarization or rather polarization scrambling as an intrinsic tissue property. 15 Equipped with these advancements, PS OCT is increasingly applied for medical diagnosis mainly in ophthalmology 9,[16][17][18] followed by dentistry, 19,20 cardiology, 6,21,22 and dermatology [23][24][25] with regard to the frequency of publications over the last years. 9 Although PS OCT has successfully shown to provide additional contrast for distinguishing pathological lesions from normal tissues, it has not been used much in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation